1992
DOI: 10.1530/jrf.0.0960309
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of interleukin 2 receptors in conceptus-derived suppression of T and B cell proliferation in horses

Abstract: Summary. The mechanism by which a horse conceptus-derived immunosuppressive factor (HCS) of Mr > 100 000 inhibits lymphocyte proliferation was investigated. The factor was obtained from the culture supernatants of 20-day-old horse conceptuses; activity, identified by reduced uptake of [3H]thymidine by mitogen-stimulated lymphocytes, was greatest (P < 0\m=.\01) in cultures stimulated by mitogen from pokeweed. HCS also suppressed cell proliferation stimulated by phytohaemagglutinin (P < 0\m=.\01), but had no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Extracts from day 80 placenta have been shown to inhibit the proliferation of maternal lymphocytes, 64 and co‐culture of chorionic girdle trophoblasts with maternal lymphocytes caused a decrease in proliferation and a reduction in cytokine production 65,66 . Also, a >100,000 kDa molecule isolated from culture supernatants of day 20 conceptuses, termed horse conceptus‐derived immunosuppressive factor, was found to inhibit lymphocyte proliferation by inhibiting IL‐2R expression 67 . Further investigation into trophoblast‐produced immunomodulatory factors is warranted, based upon the important role they play in other species.…”
Section: Mechanisms Of Maternal Tolerance To the Developing Fetusmentioning
confidence: 99%
“…Extracts from day 80 placenta have been shown to inhibit the proliferation of maternal lymphocytes, 64 and co‐culture of chorionic girdle trophoblasts with maternal lymphocytes caused a decrease in proliferation and a reduction in cytokine production 65,66 . Also, a >100,000 kDa molecule isolated from culture supernatants of day 20 conceptuses, termed horse conceptus‐derived immunosuppressive factor, was found to inhibit lymphocyte proliferation by inhibiting IL‐2R expression 67 . Further investigation into trophoblast‐produced immunomodulatory factors is warranted, based upon the important role they play in other species.…”
Section: Mechanisms Of Maternal Tolerance To the Developing Fetusmentioning
confidence: 99%
“…*^-^^ Immunosuppressive activity of the placenta has also been demonstrated in the Roth et al34 described a >30,000 kDa substance produced in culture by Day 9-20 horse embryos which was shown to suppress lymphocyte proliferation in several mitogen-stimulated blastogenesis assays, and appeared to be acting by inhibiting responses to IL-2. 35 Lea and Bolton3' found that Day 80 endometrial cup tissue extracts suppressed mixed lymphocyte responses and blastogenesis, and demonstrated that this suppression was not due to eCG. Lea et al38 recently showed that a population of the maternal leukocytes (primarily eosinophils) associated with endometrial cup tissue are positive for Transforming Growth Factor Beta-2 (TGF-P2) mRNA.…”
Section: Discussionmentioning
confidence: 98%
“…However, this question awaits further investigation. Recently, it has been reported that sIL-2R may also be produced by the conceptus [24], The expression of IL-6R is limited to a small number of cells, but soluble complexes of IL-6/IL-6R can mediate the signal through a membrane glycopro tein (gp 130), which is expressed on most cells [25], Thus, the presence of sIL-6R in RPS may imply that ubiquitous tissue targets are put under the influence of IL-6-mediated effects in pregnancy. Such accessibility of IL-6 may be a prerequisite for the occurrence of a normal placental Gynecol Obstel Invest 1996;41: [1][2][3][4]development and for the establishment of an adequate hormone production [3,26].…”
Section: Discussionmentioning
confidence: 99%